ANALISIS PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PARTISIPASI ANGKATAN KERJA, PERTUMBUHAN PENDUDUK, DAN KONSUMSI ENERGI TERBARUKAN TERHADAP PENGANGGURAN DI NEGARA ASEAN-6 DAN CHINA TAHUN 2014-2022 - Eka Ferlyana Sejati; Pratiwi Dwi Karjati; Gigih Pratomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Unemployment remains one of the structural challenges faced by nearly every country in the world. Unemployment reflects an imbalance between the growth rate of the labor force and capacity of the economy to create new employment opportunities. The ASEAN-6 region and China face particular challenges in reducing unemployment amid the dynamics of economic challenges in reducing unemployment amid the dynamics of economic growth (GDP), labor force participation rate (LFPR), population growth (PG), and renewable energy consumption (REC) on unemployment in ASEAN 6 countries and China during the 2014-2022 period. This research employs a quantitative approach using panel data covering 7 countries (Indonesia, Malaysia, Singapore, Philippines, Thailand, Vietnam, and China), with a total of 63 observations. Data were obtained from the World Bank, International Labour Organization (ILO), and International Energy Agency (IEA). The analytical method used is panel data regressions with the Fixed Effect Model (FEM). The results show that economic growth has a negative and significant effect on unemployment in ASEAN-6 countries and China. Population growth has a negative and significant effect on unemployment in ASEAN-6 countries and China. Renewable energy consumption has a negative and significant effect on unemployment in ASEAN-6 countries and China. Meanwhile, labor force participation rate has not significant effect on unemployment in ASEAN-6 countries and China. Simultaneously, the four variables have a significant effect on unemployment in ASEAN-6 countries and China.